2008
DOI: 10.1055/s-2007-1003188
|View full text |Cite
|
Sign up to set email alerts
|

Plazentalokalisation und Inzidenz der Präeklampsie

Abstract: These data suggest that a laterally located placenta is associated with a significantly increased incidence of preeclampsia, with a risk ratio of 3.1 when compared to pregnancies with centrally located placentas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 0 publications
3
20
0
Order By: Relevance
“…This result is consistent with the studies by Tania K et al 5 Anuja VB et al 6 and Pai MV et al 7 Odds ratio in this study was 3.16 i.e., there is 3.16 times higher chances of development of preeclampsia among laterally located placenta than centrally located placenta. This finding is consistent with study by Anuja VB et al 6 Kofinas AD et al 8 and Gonser M et al 9 This is also comparable with the study by Tania K et al 5 and Seadati N et al 10 where the odds ratios were 5.09 and 5.6 respectively. In the present study, hypertension was mild in most of the cases (84.5%) ( Table 6) and both mild and severe form of hypertension are more common with laterally located placenta.…”
Section: Discussionsupporting
confidence: 91%
“…This result is consistent with the studies by Tania K et al 5 Anuja VB et al 6 and Pai MV et al 7 Odds ratio in this study was 3.16 i.e., there is 3.16 times higher chances of development of preeclampsia among laterally located placenta than centrally located placenta. This finding is consistent with study by Anuja VB et al 6 Kofinas AD et al 8 and Gonser M et al 9 This is also comparable with the study by Tania K et al 5 and Seadati N et al 10 where the odds ratios were 5.09 and 5.6 respectively. In the present study, hypertension was mild in most of the cases (84.5%) ( Table 6) and both mild and severe form of hypertension are more common with laterally located placenta.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, asymmetric blood flow may be related to regional heterogeneity in the transformation of spiral arteries into low-resistance vessels (17). Other investigators have shown that when the placenta is laterally placed, volumetric flow is higher and vascular impedance lower in the ipsilateral UA and that there is an increased incidence of PE, fetal distress, Cesarean sections, and IUGR (8,19,22). Because we did not observe differences in the location of the placenta among groups or any relationship between placental location and Q UA , we concluded that altered trophoblast invasion and remodeling rather than placenta location was responsible for the asymmetry observed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have revealed side-to-side differences in uteroplacental Doppler flow in pregnancies with unilateral placentas as well as the relationship between abnormal Doppler measurements and pre-eclampsia (13)(14)(15)(16)(17)(18)(19)(20)(21). However, reports on the direct association between placental location and development of pre-eclampsia, regardless of confounding factors (22), are limited.…”
Section: Introductionmentioning
confidence: 99%